2004
DOI: 10.1084/jem.20040452
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Axonal Connections Contributes to Recovery in an Animal Model of Multiple Sclerosis

Abstract: In multiple sclerosis (MS), inflammation in the central nervous system (CNS) leads to damage of axons and myelin. Early during the clinical course, patients can compensate this damage, but little is known about the changes that underlie this improvement of neurological function. To study axonal changes that may contribute to recovery, we made use of an animal model of MS, which allows us to target inflammatory lesions to the corticospinal tract (CST), a major descending motor pathway. We demonstrate that axons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 40 publications
(68 reference statements)
3
102
0
5
Order By: Relevance
“…This hypothesis is based on the observation that, during the course of the disease, a series of plastic phenomena involving alpha motoneuron afferents correlate with a worsening of the symptoms of the disease (5). Also, a highly plastic response of the motor system after neuroinflammatory lesion was reported by Kerschensteiner et al (3), with axonal remodeling being observed at multiple levels, including the area surrounding the lesion, and above as well as inside the motor cortex (3).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This hypothesis is based on the observation that, during the course of the disease, a series of plastic phenomena involving alpha motoneuron afferents correlate with a worsening of the symptoms of the disease (5). Also, a highly plastic response of the motor system after neuroinflammatory lesion was reported by Kerschensteiner et al (3), with axonal remodeling being observed at multiple levels, including the area surrounding the lesion, and above as well as inside the motor cortex (3).…”
Section: Discussionmentioning
confidence: 95%
“…During the course of EAE, damage to the axons as well as the occurrence of synaptic plasticity phenomena in the brain and spinal cord contribute to the clinical signs of the disease (3,6,7). Synaptic plasticity in the spinal cord may explain, at least in part, the rapid sensorimotor recovery of the animals soon after tetraplegia (3,5). In view of the importance of a better understanding of MS as well as its experimental models, major advances in understanding how cellular and humoral immune responses contribute to the pathogenesis of these diseases have been made in recent years (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth-associated protein 43 (GAP-43) is an axonal phosphoprotein involved in regulating the growth state of axon terminals. These proteins have previously been studied in EAE and MS and used as indicators of neuronal damage and plasticity [24][25][26]. To obtain semiquantitative data regarding neuronal integrity and pathology, Western blotting for GAP-43 ( Figure 3iiA) and MAP2 (Figure 3iiB) was carried out on whole SCH samples from PAI-1 -/-and WT mice at different stages of CREAE.…”
Section: Fibrinolytic System In Creae 221mentioning
confidence: 99%
“…An earlier study demonstrated a 40-50% loss of CST axons at 90 and 180 days post-EAE induction via myelin-oligodendrocyte glycoprotein injection in C57/BL6 or Biozzi mice, and consistent a melioration of CST axon loss, spinal compound action potential amplitudes and areas, and clinical scores in phenytointreated animals (Black et al, 2006). In a CST local target EAE model, descending CST axons extend new collaterals above the lesion that establish a "detour" circuit to the lumbar target area, whereas below the lesion, spared CST axons increase their terminal branching (Kerschensteiner et al, 2004). The DiI tracer also is a competent candidate for monitoring such axonal restructuring in EAE model with axonal protective or repair-oriented treatment.…”
Section: Discussionmentioning
confidence: 61%